Peran Masyarakat Lokal Terhadap Pembangunan Jalur Trekking Di Desa Telaga Tawang Kecamatan Sidemen Kabupaten Karangasem (Jurnal Destinasi Pariwisata, 2025)
This research explores the involvement of local communities in the development of a trekking route in Telaga Tawang Village, Sidemen District, Karangasem Regency. The village, known for its agrarian landscape, offers unique natural and cultural potential for community-based tourism (CBT). The study aims to understand the level and nature of local community participation in the planning, implementation, and evaluation stages of the trekking trail development. A qualitative descriptive approach was employed, gathering data through in-depth interviews, observation, and documentation. Informants were selected using a snowball sampling technique, involving village officials, Pokdarwis (tourism awareness groups), BUMDes (village-owned enterprises), and local farmers. The research findings reveal that local community participation was most prominent during the implementation phase, where community members actively engaged in construction through mutual cooperation and self-funded efforts. Additionally, the community utilized the trekking route for economic benefits, including guiding services and local product sales, contributing to the village’s economic growth. However, participation in the early planning and evaluation stages was limited, with decision-making mainly driven by village leaders and tourism stakeholders. The study highlights the need for inclusive participatory mechanisms throughout all stages of development, particularly in planning and evaluation, to ensure sustainability. Strengthening community capacity through training and establishing an evaluation and maintenance team for the trekking route are crucial steps to ensure that the tourism initiative continues to thrive while maintaining cultural and environmental integrity. This research contributes to the understanding of community involvement in rural tourism development and the application of CBT principles in sustainable tourism.